The Relationship Between Listening to Music While Studying for an Examination and the Results of the Examination of Second Year Students in PLM College of Science in the Academic Year 2008-2009 - 4 0 16; 5
The study determined the relationship between listening to music while studying for an examination and the results of the examination of second year students in PLM College of Science. Eighty-nine samples were taken which included the whole sampling population except for the students who dropped out of the research. A questionnaire that was formulated by the researchers with the objectives in mind was used for the collection of data, while the final exam scores were obtained from the professors. The study design is cross-sectional, with zga (B= 90% and a minimum error of 0.10, wherein the adequate sample size is 67. The data and results were encoded, generated, and analysed using SPSS (statistical Package for the Social Sciences), and the test statistic used is point-biserial correlation (variation of Pearson correlation). Using point-biserial correlation, with a Pearson correlation of 0.062 with a number of 202 responses and with p>0.1, using two tails, a positive correlation was observed, but no statistically significant relationship exists between listening to music while studying for an examination and the results of the examination.s
Keywords: 2 -- 0; 6; 20; 20; 2